Masuknya Islam Di Nusantara: Teori, Saluran, Dan Pola Islamisasi - Nurul Jubaedah Amalia; Risma Risma; Idrus L. (FKIP UNSULTRA, 2026)
The arrival of Islam in the Indonesian archipelago was a gradual historical process influenced by various social, economic, cultural, and political factors. Studies on Islamization in the Indonesian archipelago have given rise to various theories explaining the origins of Islam, the routes of its spread, and the patterns of local acceptance of Islamic teachings. This study aims to analyze theories on the arrival of Islam in the Indonesian archipelago, the channels through which Islam spread, and the patterns of Islamization that developed in various regions of the archipelago. The study used a literature study method by examining various scientific sources in the form of books, journals, articles, and relevant historical documents. The results of the study indicate that there are several main theories regarding the arrival of Islam in the Indonesian archipelago, namely the Arab theory, the Gujarat theory, the Persian theory, and the Chinese theory. Each theory has a different basis for argument based on historical, archaeological, and cultural evidence. Furthermore, the process of spreading Islam occurred through various channels, such as trade, marriage, education, Sufism, art, and power politics. The pattern of Islamization in the Indonesian archipelago occurred peacefully, accommodating, and adaptive to local culture, so that Islam was accepted by society without causing major conflict. This process also demonstrates that Islamization was not solely religious in nature, but also influenced social, cultural, educational, and governmental transformations in the Indonesian archipelago. Thus, the arrival of Islam in the Indonesian archipelago was a multidimensional process that shaped the moderate, tolerant, and acculturated character of Indonesian Islam.